Determinan Kemampuan Auditor Mendeteksi Kecurangan - Rizki, Anggun; Mahmudi, Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to examine the effect of workload, time pressure, and personality type on the ability of auditors to detect fraud with the moderating variable of audit experience. The method used in this study is a quantitative method using primary data. This research uses multiple linear regression models with Moderated Regression Analysis to test the effect of each variable on the auditor's ability to detect fraud. The number of samples used in this study amounted to 124 auditors who work in the Jakarta and Yogyakarta Public Accounting Firms. The results show that time pressure has a negative effect, the greater the auditor's time pressure, the lower the auditor's ability to detect fraud. Personality type has a positive effect, the higher the combination of ST (sensing and thinking) and NT (intuition and thinking) personality type, the auditor's ability to detect fraud increases. According to the research results, audit experience as a moderating variable is able to strengthen the relationship between time pressure and the combination of ST (sensing and thinking) and NT (intuition and thinking) personality types on the auditor's ability to detect fraud. On the other hand, based on the results of the study, it was found that the auditor's experience as a moderating variable was not able to strengthen the relationship between workload and the auditor's ability to detect fraud. The implications of this research are aimed at the auditors should pay more attention to these factors in order to be able to improve the auditor's ability to detect fraud. This is due to prevent fraud in an entity and so that users of auditor services have confidence that the audited financial statements do not contain misstatements. Future research is expected not only to collect data by distributing questionnaires but also to interviews or oral questions.